IMPLEMENTASI SISTEM ADMINISTRASI DAN PELAYANAN AKADEMIK BERBASIS PAPERLESS OFFICE DI AKADEMI MILITER - Kurniatun, Endang Sri; Sulistyowati, Sri; Subina, Totong; Mega, Aryanti (JURNAL DWIJA KUSUMA, 2023)
“Paperless office” is an idea that emerges to save the environment by reducing the use of paper and switch it into technology. Paperless office (PLO) is a web-based application which is used to do online mailing administration and has been applied in some organizations such as universities, companies, and other administrative activities. Digital media products support changes from hardcopy to paperless, from book to flashdisk, smartphone, e-mail, e-books and others, as well as physical interaction to virtual collaboration. This research aims to spot the implementation of the administration system and academic services based on paperless office at the Indonesian Military Academy. This research uses a qualitative approach by using interviews, observations and documentations as the data collection techniques used. The research result shows that the implementation of administrative systems and academic services at Indonesian Military Academy currently uses manuals or conventional method. The Military Academy as an educational institution which can not been able to get rid of the need for paper in each work unit activities. The entire academic community of the Military Academy should commit to making well-progressing changes, it is expected that the implementation of administrative system and academic services paperless office-based in the Military Academy can be realized significantly.